2006
DOI: 10.1021/jf0618980
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Clarified Bayberry (Myrica rubraSieb.et Zucc.) Juice Sediment

Abstract: Clarified bayberry juice turned hazy upon storage at 25 degrees C for 6 months, and the chemical composition of centrifugally separated sediment was analyzed. Bayberry juice haze was mainly protein-tannin haze. The lyophilized sediment contained 20.4 +/- 4.3% of protein, 70.2 +/- 2.6% of total polyphenols, 7.2% of monosaccharides, and 6.7 +/- 0.6% of ash. Amino acid analyses and molecular weight distribution estimation indicated that bayberry proteins were haze-active proteins with a molecular weight less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 34 publications
(72 reference statements)
1
39
0
Order By: Relevance
“…Between the experimental periods, sorbitol contents, a polyalcohol resulting from glucose degradation, only varied significantly in T1, T2 and T4 (Table 3). Accordingly, a clear pattern of isomerization or hydrolysis could not be found for these sugars in juices added with chitosan (Table 3), which is an indication of a heterogeneous flocculation and removal of some soluble components during samples preparation (Fang et al, 2006), as well as a dissimilar oxidation kinetics during storage. Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Between the experimental periods, sorbitol contents, a polyalcohol resulting from glucose degradation, only varied significantly in T1, T2 and T4 (Table 3). Accordingly, a clear pattern of isomerization or hydrolysis could not be found for these sugars in juices added with chitosan (Table 3), which is an indication of a heterogeneous flocculation and removal of some soluble components during samples preparation (Fang et al, 2006), as well as a dissimilar oxidation kinetics during storage. Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…MRD is known to contain high concentration of proanthocyanidins [1]. These are condensed tannin polymers composed of various flavan-3-ol catechin units.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent study, [7] revealed the ability of oligomeric proanthocyanidins to suppress SPEBP-2 [7] and to increase PPAR-α expression. Another possibility is that the proanthocyanidins and the various poly phenols present in MRD [1,2] may act to suppress fat absorption in the intestine. Previous studies revealed the inherent ability of proanthocyanidins to decrease hyperlipidemia in mouse model type 2 diabetes [9] and in streptozotocin-induced type 1 diabetes in rats [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical investigations of the fruit juice revealed the presence of high concentrations of polyphenols and proanthocyanidins (Fang et al, 2006). The latter are con-densed tannins (polymers) composed of various flavan-3-ol or catechin units.…”
Section: Introductionmentioning
confidence: 99%